First report of Meris paradoxa Rindge (Geometridae: Ennominae) in the central mountains of Mexico, description of its female and a comparison of caterpillar variation among kin - Garzón-Orduña, Ivonne J.; Matson, Tanner A. (Zootaxa, 2021)
Meris paradoxa Rindge, thought to be restricted to southeastern Arizona, is documented in Mexico for the first time. Previously described only from males, we provide the first description of the female from specimens collected as caterpillars and reared to adults. We find female M. paradoxa to have a normal haustellum; an external diagnostic character for this species previously only confirmed in conspecific males. Female genitalia of M. paradoxa are found similar to other Meris, but the absence of a sclerotized signum (present in congeners) may prove autapomorphic. Natural history information for the genus is discussed in light of new data reported here for Mexican M. paradoxa.